Faktor Berhubungan dengan Kualitas Hidup Penyakit Ginjal Tahap Akhir Menjalani Hemodialisis - Sufiana Larombia; Siti Badriah; Fitrian Rayasari (FORIKES, 2021)
End-Stage Renal Disease (ESRD) is a category of terminal disease. ESRD is a condition where there is a gradual decline in kidney function caused by various kidney diseases. Hemodialysis is one of the most common methods of RRT used in the treatment of ESRD patients. Hemodialysis therapy will affect aspects of the life of patients with chronic kidney disease, not only affecting the physiological aspects but also on the psychological and social aspects besides that there are several comorbidities in patients with end-stage renal failure. This study was to analyze the relationship between quality of life and patients suffering from end-stage kidney disease undergoing hemodialysis. This study used a cross-sectional design. The sample used in this study were 90 patients. The results of the study with the Chi-square test stated that there was a significant relationship between age, gender, length of HD, Hb levels, blood pressure, family support and anxiety with quality of life (p